2022
DOI: 10.1002/smtd.202200583
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of WSe2/WS2/WSe2 Dual Junction Phototransistor Incorporating High Responsivity and Detectivity

Abstract: The excellent semiconducting properties and ultrathin morphological characteristics allow van der Waals (vdW) heterostructures based on 2D materials to be promising channel materials for the next‐generation optoelectronic devices, especially in photodetectors. Although various 2D heterostructure‐based photodetectors have been developed, the unavoidable trade‐off between responsivity and detectivity remains a critical issue for these devices. Here, an ingenious phototransistor based on WSe2/WS2/WSe2 dual‐vdW he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 59 publications
(93 reference statements)
1
23
0
Order By: Relevance
“…[15][16][17][18][19] Consequent 2D vdW heterostructures with engineered band alignment exhibit unique properties beyond individual components. [15,18,20] Therefore, 2D vdW heterostructures are promising for developing next-generation imaging photodetectors.To date, a variety of 2D vdW heterostructures aiming at photodetectors have been constructed, such as WSe 2 /Bi 2 O 2 Se, [21]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19] Consequent 2D vdW heterostructures with engineered band alignment exhibit unique properties beyond individual components. [15,18,20] Therefore, 2D vdW heterostructures are promising for developing next-generation imaging photodetectors.To date, a variety of 2D vdW heterostructures aiming at photodetectors have been constructed, such as WSe 2 /Bi 2 O 2 Se, [21]…”
mentioning
confidence: 99%
“…[15][16][17][18][19] Consequent 2D vdW heterostructures with engineered band alignment exhibit unique properties beyond individual components. [15,18,20] Therefore, 2D vdW heterostructures are promising for developing next-generation imaging photodetectors.…”
mentioning
confidence: 99%
“…A strong PL emission signal around 890 nm and a weak shoulder peak at 780 nm for bare WSe 2 can be clearly observed, which correspond to the recombination of indirect transition I peak and A exciton peak, respectively . Significantly, the PL peak for the overlapped DHJ region without shift undergoes quenching in consequence of the efficient separation and transition of photogenerated carriers across the heterostructures. , …”
Section: Resultsmentioning
confidence: 90%
“…Furthermore, the wavelength-dependent normalized photocurrent of DHJ devices was measured, as depicted in Figure c. It is observed that there are two photoresponse peaks at 650 and 760 nm in the DHJ device, which is close to the indirect transition A excitation peak of WSe 2 , thus indicating that the top and bottom WSe 2 layers mainly contribute to the spectral response.…”
Section: Resultsmentioning
confidence: 94%
“…The field-effect transistors (FETs) with a small number of layers of WSe 2 achieved a carrier mobility of up to 70.1 cm 2 V −1 s −1 and open-light ratio of over 10 6 , using Al 2 O 3 as the top gate (Liu et al, 2013). Therefore, heterojunctions formed by stacking WSe 2 and other 2D materials will help to improve the electronic and optoelectronic performance (Feng et al, 2022;Luo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%